A new design chart for estimating friction angle between soil and pile materials - Aksoy, Huseyin Suha; Gor, Mesut; Inal, Esen (Techno-Press, 2016)
Frictional forces between soil and structural elements are of vital importance for the foundation engineering. Although numerous studies were performed about the soil-structure interaction in recent years, the approximate relations proposed in the first half of the 20th century are still used to determine the frictional forces. Throughout history, wood was often used as friction piles. Steel has started to be used in the last century. Today, alternatively these materials, FRP (fiber-reinforced polymer) piles are used extensively due to they can serve for long years under harsh environmental conditions. In this study, various ratios of low plasticity clays (CL) were added to the sand soil and compacted to standard Proctor density. Thus, soils with various internal friction angles (phi) were obtained. The skin friction angles (delta) of these soils with FRP, which is a composite material, steel (st37) and wood (pine) were determined by performing interface shear tests (IST). Based on the data obtained from the test results, a chart was proposed, which engineers can use in pile design. By means of this chart, the skin friction angles of the soils, of which only the internal friction angles are known, with FRP, steel and wood materials can be determined easily.
Keywords: skin friction; pile materials; design chart; direct shear test; interface shear test; surface roughness